2020
DOI: 10.1136/bmjopen-2019-033069
|View full text |Cite
|
Sign up to set email alerts
|

‘I’ve always done what I was told by the medical people’: a qualitative study of the reasons why older adults attend multifactorial falls risk assessments mapped to the Theoretical Domains Framework

Abstract: ObjectivesMultifactorial falls risk assessments reduce the rate of falls in older people and are recommended by international guidelines. Despite their effectiveness, their potential impact is often constrained by barriers to implementation. Attendance is an issue. The aim of this study was to explore why older people attend community-based multifactorial falls risk assessment clinics, and to map these reasons to a theoretical framework.DesignThis is a qualitative study. Semi-structured interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Lastly, Racine et al 49 used the TDF to explore reasons older adults had for attending community‐based multifactorial falls risk assessment clinics. The authors identified many themes mentioned by participants for why they attend these clinics.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, Racine et al 49 used the TDF to explore reasons older adults had for attending community‐based multifactorial falls risk assessment clinics. The authors identified many themes mentioned by participants for why they attend these clinics.…”
Section: Resultsmentioning
confidence: 99%
“…In diesem Zusammenhang kommt Ärzten und anderem Gesundheitspersonal eine entscheidende Rolle zu, da sie regelmäßigen und langfristigen Kontakt zu diesen Personen haben und eine fachliche Einschätzung vornehmen können [19,20]. Darüber hinaus steigt die Wahrscheinlichkeit einer Programmteilnahme, wenn das Programm von behandelnden Ärzten und Therapeuten empfohlen wird [20,21]. Die erfolgreiche Identifikation sturzgefährdeter Personen könnte von den Kostenträgern mittels ökonomischer Anreize für die professionellen Leistungserbringer optimiert werden.…”
Section: Screening Durchunclassified
“…In diesem Zusammenhang kommt Ärzten und anderem Gesundheitspersonal eine entscheidende Rolle zu, da sie regelmäßigen und langfristigen Kontakt zu diesen Personen haben und eine fachliche Einschätzung vornehmen können [25,26]. Darüber hinaus steigt die Wahrscheinlichkeit einer Programmteilnahme, wenn das Programm von behandelnden Ärzten und Therapeuten empfohlen wird [26,27]. Die erfolgreiche Identifikation sturzgefährdeter Personen könnte von den Kostenträgern mittels ökonomischer Anreize für die professionellen Leistungserbringer optimiert werden.…”
Section: Bedeutung Funktioneller Assessmentsunclassified